2021
DOI: 10.1136/bmjoq-2020-001089
|View full text |Cite
|
Sign up to set email alerts
|

Early essential newborn care is associated with improved newborn outcomes following caesarean section births in a tertiary hospital in Da Nang, Vietnam: a pre/post-intervention study

Abstract: BackgroundTo improve maternal and neonatal outcomes, Vietnam implemented early essential newborn care (EENC) using clinical coaching and quality improvement self-assessments in hospitals to introduce policy, practice and environmental changes. Da Nang Hospital for Women and Children began EENC with caesarean section births to inform development of national guidelines. This study compared newborn outcomes after caesarean sections pre/post-EENC introduction.MethodsMaternity records of all live in-born hospital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…Cesarean births are well recognized as a barrier to successful breastfeeding for a number of reasons including: early separation of newborns to neonatal intensive care units (NICUs) or nurseries for observation ( 24 ), staff concerns that immediate SSC or breastfeeding will compromise the procedure, reduce the safety of mothers and babies, or add to their work burden; physical organization of the operating room; lack of coordination and communication between anesthesiology and obstetrics staff; and the belief that maternal pain after the procedure makes breastfeeding difficult ( 48 , 49 ). However, data from Vietnam and elsewhere show that SSC can be introduced successfully with cesarean section, is safe for both mothers and newborns, and can decrease NICU admissions, improve newborn outcomes, increase maternal satisfaction and exclusive breastfeeding rates ( 31 , 50 52 ). Similarly, pain following episiotomy may limit the comfort of the mother and contribute to reported breastfeeding difficulties ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cesarean births are well recognized as a barrier to successful breastfeeding for a number of reasons including: early separation of newborns to neonatal intensive care units (NICUs) or nurseries for observation ( 24 ), staff concerns that immediate SSC or breastfeeding will compromise the procedure, reduce the safety of mothers and babies, or add to their work burden; physical organization of the operating room; lack of coordination and communication between anesthesiology and obstetrics staff; and the belief that maternal pain after the procedure makes breastfeeding difficult ( 48 , 49 ). However, data from Vietnam and elsewhere show that SSC can be introduced successfully with cesarean section, is safe for both mothers and newborns, and can decrease NICU admissions, improve newborn outcomes, increase maternal satisfaction and exclusive breastfeeding rates ( 31 , 50 52 ). Similarly, pain following episiotomy may limit the comfort of the mother and contribute to reported breastfeeding difficulties ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding is not consistent with data from several studies that have demonstrated SSC to be associated with increased likelihood of exclusive breastfeeding from hospital discharge up to 6 months post birth ( 31 ). Data from early essential newborn care implementing hospitals in Vietnam have shown that SSC is associated with increased likelihood of exclusive breastfeeding at discharge in hospitals that have conducted staff clinical coaching and upgraded environments to support SSC and early breastfeeding using quality processes ( 24 , 29 , 52 ). It seems therefore that provider behaviors (e.g., unnecessary medical procedures and separation of mothers and newborns), caregiver behaviors (e.g., intention to use formula milk), and lack of an enabling environment for breastfeeding mitigate the expected effect of prolonged SSC on EBF3D, even when breastfeeding is initiated early.…”
Section: Discussionmentioning
confidence: 99%
“…This plan identified an urgent need for priority countries to incorporate and scale up early essential newborn care into routine care practices [ 27 ]. Early essential newborn care has been associated with reduced neonatal sepsis, increased rates of skin-to-skin post birth, higher rates of exclusive breastfeeding at discharge, and lower neonatal intensive care unit admissions for both vaginal and caesarean section born babies [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…With published evidence of benefits to the mother–neonate dyad, Early Essential Newborn Care (EENC) is carried out routinely. 10 Mothers are kept nil orally for 6 h and maintenance intravenous fluids continued for 24 h. Postoperative analgesia is uniform with single‐agent intramuscular Diclofenac or Pethidine. The urinary catheter is removed only 24 h after the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative management of nausea and vomiting, euvolemia, and normothermia is left at the discretion of the anesthetist team. With published evidence of benefits to the mother–neonate dyad, Early Essential Newborn Care (EENC) is carried out routinely 10 . Mothers are kept nil orally for 6 h and maintenance intravenous fluids continued for 24 h. Postoperative analgesia is uniform with single‐agent intramuscular Diclofenac or Pethidine.…”
Section: Introductionmentioning
confidence: 99%